Uncovering perceptions of lifestyle and convenience cashless payment for consumptive behavior generation Z Muslims - Halizah, Nur Aulia; M. Aris Syafi’i; Hendri Hermawan Adinugraha (Alkasb: Journal of Islamic Economics, 2024)
This study aims to explore the perceptions of Muslim Generation Z in Pekalongan regarding the convenience of cashless payments and their impact on consumer behavior within an Islamic economic framework. This qualitative study investigates the nuanced perceptions of 30 purposively sampled Muslim Generation Z individuals in Pekalongan concerning the convenience of cashless payment methods and their influence on their consumer behavior, specifically within the ethical guidelines of Islamic economics. In-depth interviews explored how this digitally native generation navigates modern consumerism while adhering to Islamic financial tenets. Findings indicate a conscious effort among participants to integrate principles like tasarruf (prudent financial management) and avoidance of israf (wasteful spending) into their utilization of cashless platforms. Features such as transaction tracking functionalities and cashback incentives are actively employed as tools for enhanced expenditure control and budget management. The study underscores the potential of cashless technology to facilitate financial practices aligned with Sharia principles, empowering Generation Z Muslims to make more informed, prudent, and ultimately responsible financial decisions in their daily transactions.